The Paradox of the Internet in Journalism in Nigeria: Between Flexibility and Accuracy Challenges - Izuogu, Kingsley Chukwemeka; Okpara, Onyekwere; Omeonu, Dennis Ugochukwu (Universitas Pattimura, 2025)
This study critically examines the role of the internet in the development of journalism in Nigeria, highlighting its benefits, drawbacks, and broader implications for the field. Grounded in the Theory of Technological Determinism and employing a Discourse Analysis approach through secondary data analysis, the research explores how digital advancements reshape journalistic practices. The findings reveal that while the internet enhances editorial flexibility and accessibility, it also creates a tension between speed and accuracy, posing significant challenges for journalism professionals. Furthermore, the study underscores the dual nature of the internet as both a catalyst for progress and a potential disruptor within the industry. By offering a nuanced analysis of these dynamics, this research contributes to the ongoing discourse on digital journalism, providing fresh insights into the evolving media landscape in Nigeria. The study’s novelty lies in its critical assessment of the internet as a “double-edged sword,” offering a comprehensive understanding of its paradoxical impact and proposing new perspectives on sustainable digital journalism practices.